Diminazene aceturate associated with sodium selenite and vitamin E in the treatment of Trypanosoma evansi infection in rats - Tonin A.A. (2011)
The aim of this study was to evaluate the utilization of a standard treatment with diminazene aceturate against the infection caused by Trypanosoma evansi, associated to sodium selenite and vitamin E. In vitro tests showed trypanocidal effect related to the treatment with diminazene aceturate and sodium selenite, but vitamin E had no harmful effect on the trypanosomes. In vivo experiments utilized a total of 72 adult outbreed females rats, separated into 9 groups (A, B, C, D, E, F, G, H and I), 8 animals each. Group A was the uninfected group; groups B to I were infected with 0.2mL of blood containing 106 trypanosomes. Parasitemia was estimated daily by microscopic examination of blood smears. Group B served as positive control; group C was treated with diminazene aceturate; group D with sodium selenite; group E with vitamin E; group F received an association of diminazene aceturate and sodium selenite; group G received an association of diminazene aceturate and vitamin E; group H received an association of diminazene aceturate, sodium selenite and vitamin E, and group I received an association of sodium selenite and vitamin E. Diminazene aceturate was administrated in a single dose on the 3rd day post infection (PI). Sodium selenite and vitamin E were administered at the 3rd and 23rd day PI. In vivo tests showed increase of longevity in groups treated with diminazene aceturate associated with sodium selenite (groups F and H). No difference was found between groups C and E, thus the vitamin E did not increase the efficacy of treatment against T. evansi when associated to diminazene aceturate. The curative efficacy of treatments was 37.5, 87.7, 37.7 and 75% to the groups C, F, G and H, respectively. Other treatments showed no efficacy. The sodium selenite when combined with chemotherapy may represent an alternative in the treatment of trypanosomosis. © 2011 Elsevier Inc.